A comparative analysis of image steganography based on DCT algorithm and steganography tool to hide nuclear reactors confidential information. (August 2018) - El_Rahman, Sahar A.
Highlights: Steganography is the practice of concealing the communication existence by hiding the traveled message in the cover image. The proposed image steganography algorithm is designed based on DCT to hide confidential information about a nuclear reactor, using the sequential embedding method in Least significant Bits (LSBs) (1-LSB & 2-LSB), low and middle frequency. The proposed image steganography algorithm composed of two major processes which are embedding and extracting of the confidential data from an image. The proposed steganography algorithm achieves a relatively high embedding capacity with no visual distortion in the resultant stegoimage. It enhances the security and maintains the correctness of the hidden data. Abstract: Steganography is the practice of concealing the communication existence by hiding the traveled message in cover media. This paper aims to study Discrete Cosine Transform (DCT) based steganography Using DC components for hiding secret bits sequentially in Least significant Bits (LSBs) (1-LSB & 2-LSB). Likewise, using low and middle frequencies to analyze their performance using PSNR (Peak Signal to Noise Ratio) and MSE (Mean Square Error). The findings indicate that the middle frequency has the larger hiding capacity and relatively better PSNR and MSE. Hence, a proposed steganographic tool based on DCT is implemented to hide confidential information about a nuclear reactor, using the sequential embedding method in the middle frequency. The findings indicate that the proposed tool supplies a relatively high embedding capacity with no visual distortion in the resultant image, whereas, enhance the security and maintains the correctness of the hidden data. Graphical abstract: